2004
DOI: 10.1001/archsurg.139.7.745
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Safe Identification of the Facial Nerve Using Palpable Landmarks

Abstract: Setting: University department of human anatomy and university hospital. Methods: A total of 40 human cadaver heads (79 facial nerves) were dissected by 2 prosectors, a surgeon with experience in the anatomy of the parotid region (J.A.P.; n = 39) and a medical student with experience in anatomical dissection and basic knowledge of the facial nerve disposition (A.M.; n=40). A 3-cm skin incision was made in the center of the triangle formed by the temporomandibular joint, the mastoid process, and the angle of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Pereira et al [ 5 ] suggested that external palpable landmarks can be used to identify the facial nerve trunk quickly and safely. In a study that involved 40 human cadavers, they proposed that a centre of a triangle formed by the temporomandibular joint, the mastoid process and the angle of the mandible allowed a fast and safe identification of the facial nerve and may be of significant help during surgery around the parotid region.…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al [ 5 ] suggested that external palpable landmarks can be used to identify the facial nerve trunk quickly and safely. In a study that involved 40 human cadavers, they proposed that a centre of a triangle formed by the temporomandibular joint, the mastoid process and the angle of the mandible allowed a fast and safe identification of the facial nerve and may be of significant help during surgery around the parotid region.…”
Section: Discussionmentioning
confidence: 99%
“…In a cadaveric study, Pereira et al suggested external palpable landmarks to identify the facial nerve and proposed that the facial nerve can be identified in the center of a triangle formed by the temporomandibular joint, the mastoid process, and the angle of the mandible. 15 Bony landmarks to identify the facial nerve were proposed in another cadaveric study. 16 The usefulness of these approaches in live surgery has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…A preauricular vertical skin incision was made over the center of the triangle formed by the temporomandibular joint, mastoid process, and angle of the mandible, which have been described as palpable landmarks used to accurately locate the facial nerve trunk. 28 The incision was curved behind the ear, similar to a modified Blair approach, and continued inferiorly along the sternocleidomastoid muscle to a level horizontal with the inferior edge of the thyroid cartilage. A horizontal incision was carried to the midline and the skin was reflected.…”
Section: Anatomical Dissectionmentioning
confidence: 99%